Berlin's forgotten future : city, history, and enlightenment in eighteenth-century Germany - Erlin, Matt (University of North Carolina studies in the Germanic languages and literatures, 2004)
"Through an analysis of the works of the Berlin Aufklarer Friedrich Gedike, Friedrich Nicolai, G. E. Lessing, and Moses Mendelssohn, Matt Erlin shows how the rapid changes occurring in Prussia's newly minted metropolis challenged these intellectuals to engage in precisely the kind of nuanced thinking about history that has come to be seen as characteristic of the German Enlightenment. The author's demonstration of Berlin's historical-theoretical significance also provides a fresh perspective on the larger question of the city's impact on eighteenth-century German culture. Challenging the widespread idea that German intellectuals were antiurban, the study reveals the extent to which urban sociability came to be seen be some as a problematic but crucial factor in the realization of their Enlightenment aims."--BOOK JACKET.